Pregnancy and Adverse Obstetric Outcomes After Hysteroscopic Resection: A Systematic Review and Meta-Analysis - Wu, Xue; Zhang, Mei; Sun, Ping; Jiang, Jing-jing; Yan, Lei (Frontiers in Surgery, 2022)
Objective Although the randomized controlled trial (RCT) of the efficacy of hysteroscopic resection in women with uterine septum has not shown any significant correlation in recent research, motivation for deeper study remains insufficient. In this study, the objective was to determine pregnancy-related outcomes, along with adverse obstetric outcomes, following hysteroscopic resection and also to determine whether women with hysteroscopic resection bear the same outcomes as women with normal uterine cavities. Search Methods From January 1995 to February 2022, a systematic literature review was conducted to identify all studies published concerning the gestation outcomes of women with and without hysteroscopic resection while comparing the gestation outcomes of women after hysteroscopic resection and with a normal uterine cavity. Our primary outcome was the live birth rate (LBR). The secondary outcomes were term delivery, preterm delivery, spontaneous miscarriage, malpresentation, cesarean section, and other adverse obstetric outcomes. Results 22 studies were included in this meta-analysis. The control groups of 14 studies were treated women, and the control groups of the other 8 studies were patients bearing a normal uterine cavity. Hysteroscopic resection was related to a higher rate of term delivery (OR=2.26, 95%CI 1.26 - 4.05), and a lower rate of spontaneous abortion (OR=0.50, 95%CI 0.27 - 0.93), and a lower rate of malpresentation (OR=0.31, 95% CI 0.19 - 0.50). Nevertheless, in comparison with the normal uterus group, the rates of preterm birth, cesarean section, and postpartum hemorrhage after resection did not return to normal levels.